Innovative Technologies in Teaching Foreign and Other Languages in Primary Education - Turdiev Zebiniso Abdullajon kizi (Genius Journals, 2022)
The article deals with the issues of innovative technologies in teaching foreign languages. To update the cognitive activity of children, it proposed to use interactive methods, such as gaming technologies, and creative tasks
Keywords: Information and communication technology; innovative pedagogy; quality of education; game technology